Управління комерціалізацією інноваційної продукції аграрного сектору - Коробка, Валентина Миколаївна (НУБіП України, 2016)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.03 – економіка та управління національним господарством. – Національний університет біоресурсів і природокористування України, Київ, 2016. У дисертації розкрито роль інноваційної продукції як економічної категорії та об’єкта управління в аграрному секторі, розглянуто передумови і сутність процесу комерціалізації інноваційної продукції аграрного сектору й основні проблеми його здійснення, обґрунтовано методичні підходи до оцінки управління комерціалізацією інноваційної продукції аграрного сектору. Досліджено вітчизняний ринок інноваційної продукції, організаційно-правові умови комерціалізації інноваційної продукції аграрного сектору, визначено оцінку впливу факторів на отримання коштів від реалізації інноваційної продукції аграрного сектору. Запропоновано стратегічні пріоритетні напрями комерціалізації інноваційної продукції аграрного сектору, сформульовано концептуальні підходи до управління комерціалізацією інноваційної продукції аграрного сектору, обґрунтовано пропозиції щодо комплексного оцінювання ефективності управління комерціалізацією інноваційної продукції аграрного сектору. Ключові слова: інноваційна продукція, комерціалізація, аграрний сектор, ефективність управління комерціалізацією інноваційної продукції, системний підхід, інноваційна стратегія
Dissertation for obtaining of the scientific degree of candidate of Economics, specialty 08.00.03 – Economics and Management of National Economy – The National University of Life and Environmental Sciences of Ukraine, Kyiv, 2016. The thesis reveals the role of innovative products as an economic category and as a subject of management in the agricultural sector, the background and the nature of the process of innovative products commercialization of the agricultural sector have been examined, as well as basic problems of its implementation, the methodical approach to the appreciation of management of innovative products commercialization of agricultural sector has been reasonably stated. The domestic market of innovative products has been investigated, the organizational and legal conditions for the commercialization of innovative products of the agricultural sector have been analyzed, as well as the influence of different factors on funds raising from the sale of innovative products of agricultural sector. Strategic priority areas of commercialization of innovative products of the agricultural sector have been proposed, the conceptual approaches to the management of the commercialization of innovative products of the agricultural sector have been formulated, and proposals for a comprehensive evaluation of the effectiveness of management commercialization of innovative products agricultural sector have been justified
Keywords: інноваційна продукція; комерціалізація; аграрний сектор; ефективність управління комерціалізацією інноваційної продукції; системний підхід; інноваційна стратегія; innovative products; commercialization; agricultural sector; anagement efficiency of the innovative products commercialization; ystem approache; innovative strategy